Community-based policing in COVID-19: a 4-P’s priorities of Vietnam’s police - Luong, Hai Thanh (Policing and society, 2021)
While the COVID-19 pandemic is still infecting without unpredictable estimations around the world, the role of law enforcement in the deal with this crisis is still debating. Mainly, among multidisciplinary research studies, the question of policing and police responses to deal with this virus is necessary to look for different approaches and several comparisons between national, regional, and international scale. This paper is the first study to introduce and analyse the model of community policing in COVID-19 in Vietnam as a new lens to balance between sensor and convince in policing. Using mixed methods research to combine between primary and secondary data in the period of five continuous phases, from January to July 2020, the study looks for how the 4-P's approach in policing of Vietnam contributed to limit the spread of the virus. Main findings pointed out that proactive activities, propaganda approaches, protective measures, and preventable forms are prioritised to implement in the community-based policing (CBP) to prevent and combat COVID-19. Depending on each scenario and relevant requirement, these four initiatives of Vietnam’s police will be conducted as flexible and harmonic as possible based on people-centred approaching. Finally, the paper identifies some practical recommendations that need further discussions to improve the effectiveness of CBP in health crisis in the future.